The evolution of insect metallothioneins. Issue 1937 (28th October 2020) - Luo, Mei; Finet, Cédric; Cong, Haosu; Wei, Hong-yi; Chung, Henry
Abstract : Metallothioneins (MTs) are a family of cysteine-rich metal-binding proteins that are important in the chelating and detoxification of toxic heavy metals. Until now, the short length and the low sequence complexity of MTs have hindered the inference of robust phylogenies, hampering the study of their evolution. To address this longstanding question, we applied an iterative BLAST search pipeline that allowed us to build a unique dataset of more than 300 MT sequences in insects. By combining phylogenetics and synteny analysis, we reconstructed the evolutionary history of MTs in insects. We show that the MT content in insects has been shaped by lineage-specific tandem duplications from a single ancestral MT. Strikingly, we also uncovered a sixth MT, MtnF, in the model organism Drosophila melanogaster . MtnF evolves faster than other MTs and is characterized by a non-canonical length and higher cysteine content. Our methodological framework not only paves the way for future studies on heavy metal detoxification but can also allow us to identify other previously unidentified genes and other low complexity genomic features.